Isolation and characterization of the phytopathogenic fungus Ilyonectria liriodendri from persimmon as a new susceptible host - Nikolett Molnár; Dóra Szabó; Adrienn Geiger; József Geml; Kálmán Zoltán Váczy; Zoltán Karácsony (PLoS ONE, 2025)
Several members of the fungal genus Ilyonectria primarily infect plants through the roots and basal stem, causing ‘black foot’ diseases, predominantly in woody plants such as grapevine ( Vitis spp.) and walnut ( Juglans regia ). In 2021, four Ilyonectria liriodendri isolates were cultured from the necrotized roots of Diospyros virginiana plants in Eger, Hungary. The isolates were identified by sequencing the ITS, β-tubulin, and partial histone H3 genes. The obtained sequences were used for phylogenetic analysis through multiple sequence alignment and the construction of a Maximum Likelihood tree, which revealed that all four isolates belonged to the species Ilyonectria liriodendri . The macro- and micromorphological variations, as well as the differences in exoenzyme production of the isolates suggested that they represent a somewhat diverse set of the same taxon. To prove their association with the symptoms observed in the host plants, the roots of one-year-old D. virginiana plants were artificially infected with conidial suspensions of the isolates according to Koch’s postulates. After 90 days of incubation in a greenhouse, 16 out of 20 inoculated plants showed necrosis in the taproots, while mock-inoculated plants remained symptomless. Necroses developed in the roots of the infected plants, and the inoculated fungi were reisolated, reinforcing their pathogenicity against D. virginiana . To the best of our knowledge, this is the first report of I. liriodendri causing disease in persimmon.